ECOBRICK SEBAGAI TEKNOLOGI TEPAT GUNA BERBASIS AKUNTABILITAS LINGKUNGAN PADA BAPUH BANDUNG GLAGAH: Ecobrick, Pengelolaan Limbah, Teknologi Tepat Guna, Akuntabilitas Lingkungan, Pemberdayaan Masyaraka - Tri Winarsih; Wahyu Tri Prambudi; Adinda Berliana Eka Aprilia; Achmad Afif Fajar Afandy; Ravenda Suwito; Sigit Prasetyo (ITEBIS PGRI Dewantara Jombang, 2026)
The problem of plastic waste at the community level is a crucial issue in the context ofsustainable development, particularly in areas lacking a structured waste managementsystem. This community service program aims to implement ecobricks as an appropriatetechnology that not only focuses on waste reduction but also fosters community-basedenvironmental accountability. The program was implemented through a one-monthCommunity Service Program (KKN) in August at Bapuh Bandung Glagah, using aparticipatory approach based on participatory action research. The program included localneeds-based planning, field observations, implementation of ecobrick practices, andassistance in simple recording of environmental activities. Results indicate changes incommunity behavior regarding waste management, increased utilization of plastic waste intofunctional products, and the emergence of initial awareness of the economic and ecologicalvalue of waste. The program also demonstrated that integrating technical practices with thedevelopment of value awareness can produce more sustainable impacts. The novelty of thiscommunity service program lies in the integration of appropriate technology with theestablishment of a community-based environmental accountability system. This model hashigh potential for replication to strengthen sustainable development at the local level.